2002
DOI: 10.1080/1042819021000006394
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Drug Resistance Profile in Childhood Acute Myelogenous Leukemia: No Drug is More Effective in Comparison to Acute Lymphoblastic Leukemia

Abstract: Therapy results in childhood acute myelogenous leukemia (AML) differ from those of acute lymphoblastic leukemia (ALL). Cellular drug resistance might be one of the reasons of therapy failure in AML. The aim of the study was the analysis of ex vivo drug resistance profile in childhood initial and relapsed AML in comparison to initial ALL. Fifty-three AML samples were tested for chemosensitivity and results were compared with those of 106 initial ALL samples. Ex vivo drug resistance was tested by means of the MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 10 publications
1
21
0
Order By: Relevance
“…Two of the most important glucocorticoids used for treating childhood ALL are PRED and DEX. Although DEX consistently shows higher antileukemic activity both in vitro and in vivo 4,[15][16][17] , PRED is used in most chemotherapy protocols due to its better toxicity profile. DEX administration is associated with higher risk of myopathy, adverse neuro-psychiatric events, osteonecrosis, sepsis, fungal infections, diabetes and pancreatitis 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of the most important glucocorticoids used for treating childhood ALL are PRED and DEX. Although DEX consistently shows higher antileukemic activity both in vitro and in vivo 4,[15][16][17] , PRED is used in most chemotherapy protocols due to its better toxicity profile. DEX administration is associated with higher risk of myopathy, adverse neuro-psychiatric events, osteonecrosis, sepsis, fungal infections, diabetes and pancreatitis 7 .…”
Section: Discussionmentioning
confidence: 99%
“…DEX administration is associated with higher risk of myopathy, adverse neuro-psychiatric events, osteonecrosis, sepsis, fungal infections, diabetes and pancreatitis 7 . Several studies, including ours [4][5][6]16 , have shown that leukemia cells from different patients can exhibit different responses to PRED and DEX. However, the development of personalized glucocorticoid therapies based on the in vitro response of leukemia cells to individual glucocorticoids is clinically challenging because of time constrains (MTT assay would delay onset of therapy for minimum 4 days).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies suggest that the intrinsic resistance in many tumor types, including acute myeloid leukemia (AML), is closely associated with the capacity to undergo robust cell cycle arrest in G 2 /M. [1][2][3] Generally, prolonged cell cycle arrest following DNA damage relies on p53-dependent mechanisms leading to increased expression of cell cycle regulators such as p21 and 14-3-3s. 4,5 However, a subset of tumor cells with nonfunctional p53 is also able to undergo DNA damage-induced G 2 arrest mediated by the DNA damage checkpoint.…”
Section: Introductionmentioning
confidence: 99%
“…1, P=0.010). However, differences in each drug sensitivity were not significant between clinical responder and nonresponder in both this study and other studies [20].…”
Section: Discussionmentioning
confidence: 45%
“…For AML, high in vitro drug resistance could partially explain unfavorable clinical results of therapy, when compared to ALL [1,20]. One of the reasons for the poor therapeutic outcomes may be cellular drug resistance to chemotherapy.…”
Section: Discussionmentioning
confidence: 99%